扶贫与发展的有效结合——浙江省扶贫实践探索及其对2020年后中国扶贫战略的启示 - Jianying, Wang; Chen, Kevin Z.; Jieying, Bi (Zhejiang University, 2020)
With a large rural population, high poverty rate, and low level of economic development during the early stage of reform and opening up, Zhejiang province successfully eliminated poverty by its own definition of annual family income per capita below 4 600 RMB, which is twice the national poverty line, by 2015. The province’s rural poverty governance leads the development of national poverty relief policies. Based on the framework of ″poverty alleviation and development″, rural poverty governance in Zhejiang province has been closely integrated with economic development. This includes elimination of households in absolute poverty, alleviation of relative poverty in rural areas, and implementation of an integrated rural-urban minimum living standard. This article discusses Zhejiang Province’s governance and policy innovation of targeted poverty reduction from six perspectives: (1) cooperative poverty reduction mechanisms in sectors of government, market and social power; (2) identifying and improving an accurate poverty identification system; (3) shifting the focus of poverty standards from absolute poverty to relative poverty; (4) transforming the main poverty reduction method from development-oriented poverty reduction supported by special funds, to poverty alleviation by means of social protection; (5) expanding the scope of poverty reduction from rural areas alone to rural-urban integration; and (6) addressing unbalanced development in the province with multiple public financial support mechanisms. Judging from the current practices and experiences of rural poverty governance for targeted poverty reduction in Zhejiang Province, the following problems may be encountered in post-2020 poverty reduction in China: (1) rural-urban-integrated poverty reduction requiring institutional innovation in poverty governance; (2) poverty governance concerning migrant workers in the context of labor transfer needs urgent attention; (3) household registration requirements in the identification of poor households generating in accurate poverty data; (4) a rural-urban-integrated minimum living standard should be adjusted for differences in cost of living in different places. The article proposes four key strategies for post-2020 poverty reduction in China, including (1) coordinating government, market and the public agencies with the aim of poverty reduction; (2) formulating a new poverty standard under the concept of relative poverty governance; (3) establishing a rural-urban-integrated poverty governance system; and (4) developing a social security system based on rights and fairness.